"Hikayat Sang Kancil" revisited: a formalistic perspective of the first made in Malaysia cartoon animation / Azhar Harun and Mohamed Razeef Abd Razak - Harun, Azhar; Abd Razak, Mohamed Razeef (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2011)
In 1983, Radio Televisiyen Malaysia (RTM) premiered an animation short titled Hikayat Sang Kancil produced by Filem Negara Malaysia (FNM) (Hassan Abd Muthalib, 2007). This particular animation was done single-handedly by Anandam Xavier, an artist at the art department of FNM, and is recognized by local researchers as the first made in Malaysia cartoon animation (Muliyadi Mahamood, 2003; Hassan Abd Muthalib, 2007; Ahmad Rafi, 2008). Adding to this achievement, 2 more episodes (directed by Hassan Abd Muthalib) were produced later, Sang Kancil & Monyet (1984) and Sang Kancil & Buaya (1986). However, after the last episode, the series were never to be seen again. After more than 30 years, surprisingly there has not been any research that discusses the production and visual meaning of Hikayat Sang Kancil. Therefore, this study attempts to examine Hikayat Sang Kancil cartoon animation using a mixed method, compositional interpretation (Monaco, 2000) and content analysis (Rose, 2007). Basically, the aim is to establish an understanding regarding to the relationship between cinematic form and visual meaning (metaphor). In addition, personal recollection from two Malaysian animation pioneers, Goh Meng Huat and Hassan Abd Muthalib were also obtained to build historical foundation. Our analysis reveals that Hikayat Sang Kancil possesses strong interplay between cinematic form and visual meaning. These findings not only suggest the co-existence of both activities; they may actually reinforce one another.